FIXED POINT RESULTS FOR COUPLINGS ON ABSTRACT METRIC SPACES AND AN APPLICATION - Aydi, Hassen; Felhi, Abdelbasset; Afshari, H.; Marasi, H. R.; Isik, Hüseyin (UNIV PRISHTINES, 2018)
Recently, Choudhury et al. [13] introduced the concept of couplings between two nonempty subsets in metric spaces. The aim of this paper is to prove the existence and uniqueness of strong coupled fixed points for a class of couplings in the context of cone metric spaces. Our results unify and generalize many know results in literature. Some examples are provided to illustrate the obtained results.
Keywords: Coupling; strong coupled fixed point; cone metric space